Gender, Culture and Power in African and Middle Eastern Works - Prakoso Liemrian Wibowo (Morphosis: Journal of Literature, 2025)
This paper explores the intricate social, political, and cultural issues in African and Middle Eastern literature through the works of Fatima Mernissi (Teras Terlarang), Ibrahim Fawal (My Salwa My Palestine), and Carmen bin Laden (Inside the Kingdom). It examines the intersection of gender, power, and identity within socio-political contexts shaped by historical struggles, patriarchal norms, and cultural expectations. The study aims to analyze how these literary works portray both personal and collective resistance against oppression while reflecting broader societal conflicts. Employing a qualitative literary analysis method, it focuses on textual interpretation and thematic exploration. Data is gathered through close reading of the selected texts, supported by secondary sources on feminist, postcolonial, and cultural theories. The analysis uncovers recurring themes of identity negotiation, resistance to patriarchal and colonial structures, and the pursuit of personal freedom within restrictive cultural environments. It highlights how literature serves as a platform for addressing sensitive socio-political issues while advocating for change. Ultimately, the study concludes that these narratives extend beyond individual struggles, offering valuable insights into the broader discourse on human rights and justice in the Islamic world. This research contributes to a deeper understanding of gender, culture, and political complexity in contemporary literature.